Keterampilan komunikasi pada anak-anak muda dengan gangguan emosi di Kupang - Kiling-Bunga, Beatriks Novianti; Halla, Oktovianus; Kiling, Indra Yohanes (Konsorsium Psikologi Ilmiah Nusantara, 2016)
Young children with disabilities are a group that is prone to stigma anddiscrimination. Therefore, World Health Organization and United Nations Children’sFund declared a global agenda in 2012 to address the needs of inclusive ECCD to improve the participation and development of young children with disabilities. In respond to that agenda, it is crucial to understand the particular needs of young children with emotional disorder such as their communication ability, before they can be included into inclusive ECCD service. This research aims to describe the communication skills of young child with emotional disorder in Kupang, Nusa Tenggara Timur. The participant in this study showed insignificant performance in verbal communication skills like linguistic content, structures and the use of language. Meanwhile in non verbal communication skills such as face expression, body gesture and hand gesture, the child showed considerable performance. The research method used qualitative method, which is direct observation to the child and interview to thesubject’s parents. Parents and ECCD tutors should consider to set a communication- stimulating relationship in house and ECCD post to support the verbal skills development. The result of this study can give impact in the development of inclusive ECCD science in East Nusa Tenggara, also to aid future research in inventing best practice models in the field.